2018
DOI: 10.1007/s40571-018-0193-8
|View full text |Cite
|
Sign up to set email alerts
|

Voidage correction algorithm for unresolved Euler–Lagrange simulations

Abstract: The effect of grid coarsening on the predicted total drag force and heat exchange rate in dense gas-particle flows is investigated using Euler-Lagrange (EL) approach. We demonstrate that grid coarsening may reduce the predicted total drag force and exchange rate. Surprisingly, exchange coefficients predicted by the EL approach deviate more significantly from the exact value compared to results of Euler-Euler (EE)-based calculations. The voidage gradient is identified as the root cause of this peculiar behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Both grids were uniform in the area of interaction between the hot jet and water droplets. The uniform grid remedied numerical problems arising in water-gas interaction region described in the paper [44].…”
Section: Asmentioning
confidence: 99%
“…Both grids were uniform in the area of interaction between the hot jet and water droplets. The uniform grid remedied numerical problems arising in water-gas interaction region described in the paper [44].…”
Section: Asmentioning
confidence: 99%
“…Otherwise the drag force of the particulate phase is not calculated correctly. Askarishahi et al [32] indicate that when flow details around individual particles are not resolved, the mesh cell size varies between 2 and 15 times the particle diameter.…”
Section: Setup Of the Simulationsmentioning
confidence: 99%
“…They found that the global averaging drag forces are clearly different from the homogeneous drag law and the deviations are related to the angles between the flow directions and ∇ϕ s . Askarishahi et al considered the influence of the volume fraction jumps on the interphase drag force in coarse-grid simulation by a voidage correction model. Su and Zhao as well as Li et al considered the influence of the unresolved structure on drag force by different assumptions of the sub-scale solid phase distributions.…”
Section: Introductionmentioning
confidence: 99%